Verbal communication disorders in a patient with diagnosed progressive supranuclear palsy - Gliwa-Patyńska, Renata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2021)
Progressive supranuclear palsy [Steele-Richardson-Olszewski] is a neurodegenerative disease of the central nervous system. It develops mainly in men over 40 years of age. The course of PSP is rather characteristic: motor, cognitive and non-cognitive impairments develop at a fairly rapid rate. The aim of the study is to assess interactional, communicative and linguistic competencies and skills, executive abilities (breathing, phonation and articulation) as well as primary functions of a patient diagnosed with PSP. The article confirms the thesis that dementia disorders overlap with motor disorders in the course of PSP.